Antiaging Activity Of Polyphenol Rich Calophyllum Inophyllum Fruit Extract In Aging Mutants Of S. Cerevisiae - S. Venugopal, Kavilasha (2022)
Calophyllum inophyllum L. is an important medicinal plant with many ethnomedicinal values and exhibited significant anti-oxidant activity. Hence, this study was conducted to determine the in vitro anti-aging property of C. inophyllum fruit extract (CIFE) against Saccharomyces cerevisiae BY611 Strain with the molecular mechanism of the anti-aging process. The anti-aging effect of CIFE against the yeast was evaluated through chronological lifespan assay, anti-oxidative stress assays, real-time quantitative polymerase chain reaction (RT-PCR) to study the regulation of superoxide dismutase (sod) and sirtuin 1 (sirt1) genes and superoxide dismutase enzyme (SOD) and sirtuin 1(SIRT1) protein activity assays were conducted at 1 mg/mL of CIFE. After administrating CIFE, the lifespan of the yeast was significantly prolonged in comparison with the untreated group (P<0.05) and also increases the yeast cell viability under oxidative stress by 4 mM H₂O₂ by spot assay. The Phloxine B stain method also further proves yeast cells' viability increased under oxidative stress by CIFE treatment. The reactive oxygen species (ROS) assay revealed that CIFE notably reduces the oxidative stress in treated yeast cells (P<0.05) comparing to untreated yeast cells.